Pediatric pulmonary services in Saudi Arabia - Abdullah A Yousef; Abdullah S Al-Shamrani; Sami A Al-Haider; Yazan S Said; Saleh Al Harbi; Adel S Al-Harbi (Annals of Thoracic Medicine, 2013)
Objective: The purpose of this study was to assess the available pediatric pulmonary services, in terms of workforce, resources, and distribution across Saudi Arabia. This would help in proper utilization of resources and direct future planning. Methods: A cross-sectional survey among pediatric pulmonologists registered in the Saudi Thoracic Society. Results: Among 43 practicing pediatric pulmonologist in Saudi Arabia, 29 have responded to the survey (response rate of 67.4%). The majority of practicing pediatric pulmonologists were young graduates with less than 5 years′ experience (44.8%) and were North American training programs graduates (69%). The majority of the respondents (51%) were located in Riyadh, 27% in Jeddah, 14% in the Eastern region and 3% in Madinah and Al-Majma′a. Most of the respondents had access to basic diagnostic tools required in the subspecialty, a majority of them (85%) lack dedicated pediatric pulmonary function laboratories. Nearly, 80% of the hospitals performed less than 50 flexible bronchoscopies/year. Conclusion: Pediatric pulmonology is a growing subspecialty in Saudi Arabia with well-trained and experienced physicians. Our study represents an overview of the available pediatric pulmonology services in Saudi Arabia, which would help in future planning and better utilization of the available resources.